Structure and bandgaps of small range gallium arsenide nanocluster - Musa, Nor Muniroh; Mt. Isa, Ahmad Radzi; Kasmin , Mohd Khalid (Ibnu Sina Institute, Faculty of Science, 2008)

(untitled)
There is currently a lot of excitement about Gallium Arsenide nanoclusters due in part to the prediction that small-enough GaxAsy clusters will act as â€œquantum dotâ€? whose bandgaps can be tuned by varying the cluster size. Small range GaAs clusters ( x + y â‰¤10) were studied by using first principles calculation where structural properties and bandgap were investigated. We obtained the results of bandgap which are larger than the simulated bandgap of bulk GaAs. In this paper, we discuss the effect of GaAs cluster size to the energy bandgap